SPECIFICS OF THE FORMING OF THE COMPETENCIES OF THE FUTURE HISTORY TEACHERS - Starodubets, Galyna; Vlasyuk, Igor; Mishchuk, Galyna; Buravsky, Olexandr; Shevchuk, Andrii (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The aim of the article is to define the specifics of formation of future history teachers’ professional competencies. Research competencies are seen among preferential ones, which are to be acquired by higher education applicants of the educational qualification Master in Secondary Education (History). The empirical basis of the research is the results obtained by instructors of the Department during teaching the special courses “History of Stalinism” and “History of New Independent States”. The article highlights methodological techniques and practices, implemented by educationalists in the process of teaching the mentioned special courses, aiming at forming professional competencies of students obtaining Master’s degree. Using the materials of the laboratory “Studying the Soviet Past of the Stalin’s Era” (audio and video recordings of interviews with women from villages in Zhytomyr Region, who were raised in the conditions of the Stalin’s regime) is the peculiarity of the educational process. The focus of attention is the methodology of organization of students’ work with archive sources, scientific literature and narrative texts.